PERBANDINGAN MODEL PEMBELAJARAN INKUIRI DAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN BERFIKIR KRITIS MURID PADA MUATAN PEMBELAJARAN IPS KELAS V SEKOLAH DASAR - Tabrani; Idawati; Muhammad Basri (Jurnal Pendidikan Dasar, 2022)
The purpose of the study was to determine the differences between the inquiry learning model and the problem based learning model assisted by audio visual media on the critical thinking skills of students in class V social studies subject matter. This type of research was a pretest-posttest control group design. The number of samples in this study were fifth grade students at SDN 1 Padduppa in the control class and SDN 260 Lapongkado in the experimental class. Data collection methods used are learning outcomes tests to measure students' critical thinking skills and documentation. The data analysis technique used is descriptive statistical approach and inferential analysis. Research results From this ttable value can be written as follows: ttable with a significance level of 5% = 2.0129 > tcount of = 1.379. So it can be concluded that there is no significant difference between the inquiry learning model and the problem based learning (PBL) model with the aid of audio visual media on students' critical thinking skills in class V social studies learning content